The first trimester human placenta is a site for terminal maturation of primitive erythroid cells - Van Handel, Ben (American Society of Hematology, 2010)
Embryonic hematopoiesis starts via the generation of primitive red blood cells (RBCs) that satisfy the embryo's immediate oxygen needs. Although primitive RBCs were thought to retain their nuclei, recent studies have shown that primitive RBCs in mice enucleate in the fetal liver. It has been unknown whether human primitive RBCs enucleate, and what hematopoietic site might support this process. Our data indicate that the terminal maturation and enucleation of human primitive RBCs occurs in first trimester placental villi. Extravascular ζ-globin(+) primitive erythroid cells were found in placental villi between 5-7 weeks of development, at which time the frequency of enucleated RBCs was higher in the villous stroma than in circulation. RBC enucleation was further evidenced by the presence of primitive reticulocytes and pyrenocytes (ejected RBC nuclei) in the placenta. Extravascular RBCs were found to associate with placental macrophages, which contained ingested nuclei. Clonogenic macrophage progenitors of fetal origin were present in the chorionic plate of the placenta before the onset of fetoplacental circulation, after which macrophages had migrated to the villi. These findings indicate that placental macrophages may assist the enucleation process of primitive RBCs in placental villi, implying an unexpectedly broad role for the placenta in embryonic hematopoiesis.